EFFETS DE DEUX PHYTOHORMONES EXOGENES ET DU NACL SUR LA MORPHOGENESE IN VITRO D’OCIMUM CANUM SIMS - Essozima, Aliaki; Djidjole, Etse Kodjo; Kodjo, Glato; Rassimwaï, Pitekelabou; Koffi, Koba; Atsou, Aïdam (European Scientific Journal, ESJ, 2014)
In vitro regeneration of Ocimum canum has been possible by the use of micropropagation methods. The seeds need the light to germinate. The plantlets obtained from the germinated seeds are used for the micropropagation. The plantlets are sliced in to single nodal fragments and grown on the Murashige and Skoog basic medium containing Indol-butyric acid (IBA), Benzylaminopurine (BAP) and sodium chlorite. The results have shown that the Murashige and Skoog medium favored the normal growth of the vitroplants of Ocimum canum. The Indol-butyric acid (IBA) facilitated the plants rooting with a maximum of 25 roots/vitroplant at the concentration of 3 mg/L. The Benzylaminopurine (BAP) increased the multiplication rate. The combination of the IBA and the BAP induced organogenetics callus which initiated roots. The sodium chlorite (NaCl) at the concentration of 5 g/L inhibited the growing of the vitroplants. Rooted plantlets were successfully acclimatized at a rate of 100%.